BUREAUCRATIC STRUCTURE PERESTROIKA: MEMPERBARUI LAHAN BAGI PERTUMBUHAN KINERJA KELEMBAGAAN PEMERINTAH - Haris Faozan1 (Sekolah Tinggi Ilmu Administrasi Lembaga Administrasi Negara, 2004)
Bureaucracy as a terminology began to be widely known after Max Weber (1864-1920) introduced a model of organization known as bureaucratic organization. In his elaboration, Weber states that the form of bureaucratic organization is a type of organization that most fits the characteristics of industrial society in the late 19th century, both public and private sectors. The bureaucratic structure has existed for almost 100 years and, of course, it now requires some adjustments here and there in order to make its existence intact as Max Weber intended in building such phenomenal theory of bureaucracy. The structure of quality public sector is the one able to adjust to endless challenges. Such adjustable structure will enable public sector performance to grow and proliferate optimally. It is, therefore, necessary to keep readjusting certain dimensions of such organizational structure as complexity, formalization and centralization to the present conditions.